DESIGN EKONOMIS UNTUK PROPELLER KAPAL - Hartono Hartono (Diponegoro University, 2008)
Increase of the price of world oil pushs liner to conduct action is economic from every operational unit in it’sship armada. One other most dominant in usage of fuel is Main engine is working to turn around propeller asship actuator. On that account ship owner wants design propeller which is economic for it’s ship to canreduce usage of fuel of 20% when sailing.